A compact 60 GHz LTCC microstrip bandpass filter with controllable transmission zeros - Meng, Fanyi (2013)
This paper presents a compact microstrip bandpass filter (BPF) with separate electric and magnetic coupling paths (SEMCPs) for 60 GHz applications. Either electric or magnetic coupling can be dominant in the total electromagnetic coupling, while the location of transmission zeros differs. The proposed fourth-order BPF is designed based on two metal layers of a 85 μm LTCC substrate. Without any via connections, the design configuration is very simple which facilitates the crafts of fabrications. The filter achieves a center frequency of 60.275 GHz, a 3-dB bandwidth of 3.15 GHz (5.22%), and a compact size of only 1.3 × 0.74 mm2. The minimum insertion loss of the filter is 2.7 dB and the return loss is better than 17 dB in the passband.